2018
DOI: 10.1038/s41598-018-33622-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing for investigations of meningococcal outbreaks in the United States: a retrospective analysis

Abstract: Although rare in the U.S., outbreaks due to Neisseria meningitidis do occur. Rapid, early outbreak detection is important for timely public health response. In this study, we characterized U.S. meningococcal isolates (N = 201) from 15 epidemiologically defined outbreaks (2009–2015) along with temporally and geographically matched sporadic isolates using multilocus sequence typing, pulsed-field gel electrophoresis (PFGE), and six whole genome sequencing (WGS) based methods. Recombination-corrected maximum likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…To evaluate BioHansel's SNP-detection accuracy, we compared its concordance with Snippy (Seemann, 2015), a traditional SNP-detection workflow. We chose to compare BioHansel with Snippy as it is popular, built for speed, and has demonstrated accuracy that compares favourably to other traditional SNP-detection workflows (Whaley et al, 2018).…”
Section: Biohansel's Genotyping Results Have High Concordance With Trmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate BioHansel's SNP-detection accuracy, we compared its concordance with Snippy (Seemann, 2015), a traditional SNP-detection workflow. We chose to compare BioHansel with Snippy as it is popular, built for speed, and has demonstrated accuracy that compares favourably to other traditional SNP-detection workflows (Whaley et al, 2018).…”
Section: Biohansel's Genotyping Results Have High Concordance With Trmentioning
confidence: 99%
“…The choice of typing approach depends on its intended application (for a review see Nadon et al, 2017), although in general, gene-by-gene approaches are popular for routine surveillance activities, whereas SNP-based approaches are used when extra discriminatory power is required, or for pathogens that are not amenable to gene-by-gene methods. Comparisons of gene-by-gene and SNP-based approaches show that these methods both produce concordant and complementary results Whaley et al, 2018;Jagadeesan et al, 2019). Regardless of the method used, the analysis of WGS data can be highly complex and can require high performance computing and specialized genomics expertise to carry out and to interpret the results (Carriço et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of the studies, subtyping of N. meningitidis is being carried out using a wellestablished cgMLST scheme, developed by Jolley et al (2018). Recently, a number of works have also applied assembly-, kmerand mapping-based SNP approaches in some cases combined with recombination detection tools, for characterization of N. meningitidis (Figure 1) (Lamelas et al, 2014(Lamelas et al, , 2017Mustapha et al, 2015;Sater et al, 2015;Stefanelli et al, 2016;Bårnes et al, 2017;Diallo et al, 2017;Tzeng et al, 2017;Hao et al, 2018;Whaley et al, 2018). However, it is not always that clear which method is the best to use for a given research question Whaley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of works have also applied assembly-, kmerand mapping-based SNP approaches in some cases combined with recombination detection tools, for characterization of N. meningitidis (Figure 1) (Lamelas et al, 2014(Lamelas et al, , 2017Mustapha et al, 2015;Sater et al, 2015;Stefanelli et al, 2016;Bårnes et al, 2017;Diallo et al, 2017;Tzeng et al, 2017;Hao et al, 2018;Whaley et al, 2018). However, it is not always that clear which method is the best to use for a given research question Whaley et al, 2018). Several studies demonstrated a high degree of agreement between the different SNP-based approaches and cgMLST on distinguishing epidemiologically linked isolates (Bårnes et al, 2017;Diallo et al, 2017;Whaley et al, 2018), but no detailed evaluation has been carried out describing the differences in performance and output of cgMLST and SNP-based workflows, and how they are affected by the use of tools that detect and mask recombinant regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation